Pengaruh Komunikasi Internal, Lingkungan Kerja dan Motivasi terhadap Employee Engagement: (Studi pada Koperasi Mitra Dhuafa Jakarta Selatan) - Irsyad Jauharul Haq; Widi Wahyudi (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Employee Engagement is a positive thing, where employees are enthusiastic about working and achieving company goals. This research aims to examine the influence of Internal Communication, Work Environment and Motivation on Employee Engagement among Employees at the South Jakarta Mitra Dhuafa Commission Institute. This research used a non-probability sampling technique with a saturated sampling type, taking 99 employees of the South Jakarta Mintra Dhuafa Commission Institute as respondents in this research. Data analysis was carried out through multiple linear regression using SPSS version 22 software. The results of this research show that the Internal Communiaction and Motivation variable has a positive and significant influence on Employee Engagement. Meanwhile, the Work Environment variables do not have a significant influence on Employee Engagement. It is hoped that the results of this research can increase employee engagement at the South Jakarta Mintra Dhuafa Commission Institution.